The Pentecostal Prosperity Message and Inter-Church Proselytism in Southeast Nigeria - Nwadialor, Kanayo; Nwokocha, Benjamin C. (OKH Journal: Anthropological Ethnography and Analysis Through the Eyes of Christian Faith, 2023)
The rate at which Christians in southeast Nigeria migrate from one Christian denomination to another calls for scholarly investigation; this migration is noticeable from the main-line churches to the Pentecostal groups. This study was conceived to interrogate this proselytizing venture with the view to finding the causative factors behind the inter-church movement. The study employed qualitative research methods on primary and secondary sources of data collection. Findings show that the prosperity message of the Pentecostal movement is a major player in proselytism. The continuing rise of Pentecostal groups in southeast Nigeria and the unbridled desire of some Christians for health and material prosperity give rise to the inter-church movement. The study further discovered that some Pentecostal pastors take advantage of the economic hardships in southeast Nigeria, particularly since the Nigeria-Biafra war, to manipulate the people into believing that religion, especially Pentecostalism, has solutions to all human health and economic challenges. Worried that the practice is aggressively attacking the cherished Christian kerygmatic understanding of the Church, the study recommends some practical steps that could be undertaken to save Christians from this seeming “holy deceit” as well as to rescue the image of the universal Church from being associated with religious commercialization.
free
Keywords: Pentecostal; Prosperity Preaching Inter Denominational Migration